Philosophical capacity of mysticism within medieval tradition - Терехова, Л. В. (Proceedings of the National Aviation University Series Philosophy Cultural, 2016)
The various approaches to interpretation of the term «mysticism» are analyzed in the article, the necessity of methodological distinctionof the terms «mystics» and «mysticism» for historical and philosophical studies of intellectual tradition of the Middle Ages issubstantiated; it is proved the essential theoretical achievements of mysticism and their importance for the reconstruction of discourse ofmedieval philosophy.